Determinants of Academic Performance of BBA Students: A Case of Pokhara University Affiliated Colleges - Khanal, Saroj (Nepalese Journal of Management, 2024)
This study examines the determinants of academic performance a case of BBA students of Pokhara University. Academic performance is the dependent variable. The selected independent variables are intelligence and cognitive abilities, motivation and self efficiency, learning style and strategies, emotional intelligence and well-beings, and time management. The primary source of data is used to assess the opinions of respondents regarding intelligence and cognitive abilities, motivation and self-efficiency, learning style and strategies, emotional intelligence and well-beings, and time management. The study is based on primary data of 131 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of determinants of academic performance of BBA students: A case of Pokhara University affiliated colleges.The study showed a positive impact of intelligence and cognitive abilities on academic performance. It indicates that increasing cognitive abilities of student leads to increase academic performance. Similarly, the study showed a positive impact of motivation and self efficiency on academic performance. It indicates that higher motivation leads to increase academic performance. Likewise, the study also revealed a positive impact of learning style and strategies on academic performance. It indicates that effective learning style and strategies leads to increase academic performance. Further, the study observed a positive impact of emotional intelligence and well-beings on academic performance. It indicates that emotionally stability leads to increase academic performance. In addition, the study observed a positive impact of time management and study habits on academic performance. It implies that effective time management increase academic performance.